Wireless electronic handbag (WEHB) - Mohtar @ Mokhtar, Muhammad Husaini (2003)
According to the Crime Investigation Department of the Royal Malaysian Police statistic, from January to June 2003, it is showed that there were 8,700 reported snatch theft cases in our country. From that, only 49% of this cases are solved. This cases is also become more tragedies whenever some of the snatch theft, is more brave to use a sharp weapon whenever they attack their victims. This phenomenon is not stop until we take a serious action to prevent this situation from happen again. Therefore, as an University of MARA Technology student, it has encourage us to contribute our knowledge to create a new invention known as a Wireless Electronic Handbag (WEHB). As a user of this handbag, they will not to worried anymore about yelling for help, get injured or struggled with a violent of snatch thief.